Pengaruh Sertifikasi Profesi dan Kompetensi Terhadap Kinerja Guru Madrasah Ibtidaiyah Negeri di Provinsi Lampung - Septuri, Septuri; Fradito, Aditia; Fadilah, Kharis; ilhami, ilhami (Universitas Islam Negeri Raden Intan Lampung, 2024)
The research aims to analyze the effect of certification and professional skills on teacher performance in Madrasah Ibtidaiyah Negeri (MIN) Lampung Province. Teacher professional certification is the government's effort to improve the quality of teachers through formal recognition of their skills. Teacher competency includes pedagogical, personal, social and professional skills. Teacher performance is measured based on their ability to plan, implement and value learning. This research uses a quantitative approach with survey methods. The research population consisted of certified MIN teachers from Lampung Province. The sampling technique is probability sampling. Data collection was carried out using a questionnaire which was tested for validity and reliability. Data analysis uses multiple regression techniques to examine the effect of certification and professional skills on teacher performance. The results of this study indicate that professional certification has a partial effect on teacher performance with a significance of 0.024 and competence has an effect on teacher performance with a significance of 0.000. The certification and competence variables simultaneously have an influence of 63.2% on teacher performance. These results are expected to provide empirical insight into the contribution of certification and professional skills in improving the performance of MIN teachers in Lampung Province, as well as provide suggestions to policy makers in efforts to improve the quality of education.